PRENATAL DIAGNOSIS RESULTS OF FETUSES WITH ISOLATED VENTRICULAR SEPTAL DEFECT AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the characteristics of ventricular septal defects on fetal echocardiography and to evaluate the genetic results of fetuses with isolated ventricular septal defects.Materials and methods: A cross-sectional descriptive study was conducted on 139 pregnant women with fetuses diagnosed with isolated ventricular septal defects at Hanoi Obstetrics and Gynecology Hospital from July 1, 2022, to June 30, 2024.Results: The mean gestational age at detection was 25.74 ± 5.77 weeks. Regarding prenatal screening, 4.3% of fetuses had increased nuchal translucency, and 4.2% had high-risk screening test results. On ultrasound, the mean defect size was 2.92 ± 1.31 mm, with the majority being small defects < 4 mm (81.3%). The most common locations were perimembranous (51.1%) and muscular (42.4%). The amniocentesis rate was 25.2% (35/139). Genetic analysis revealed 8 abnormal cases (accounting for 22.9% of amniocentesis cases), including Trisomy 18, Trisomy 21, and DiGeorge syndrome.Conclusion: The majority of cases were small defects (< 4 mm). The most common locations were perimembranous and muscular. The rate of detecting genetic abnormalities in the amniocentesis group was relatively high, with most abnormal cases having high-risk screening results or increased nuchal translucency.
Keywords: Isolated ventricular septal defect, prenatal diagnosis, fetal echocardiography.